Socioeconomic inequality in global incidence and mortality rates from COVID-19: an Ecological study (2020)
Objective: Coronavirus disease is an infectious disease caused by a newly discovered coronavirus. Epidemiological and clinical features of patients with COVID-19 have been examined but Socio-economic aspects of the issue have been less studied. Thus this study aimed to identify the role of human development index (HDI) in the incidence and mortality rates of COVID-19 worldwide. Methods: Information of the incidence and mortality rates of COVID-19 was obtained from the Worldometer and data about the HDI 2019 were obtained from the World Bank database. The correlation between incidence, mortality rates, and the HDI parameters were assessed using linear regression. We calculated concentration index (CI) to measure socioeconomic inequality in COVID-19 related mortality & incidence. Results: linear regression analysis showed a direct significant correlation between the incidence and mortality rate from COVID-19 and HDI at the global level. The concentration index was positive for incidence rate (0.62) and mortality rate (0.69) of COVID-19, indicating the higher concentration of the rates among groups with high HDI. Conclusions: The high incidence and mortality rates of COVID-19 in countries with high and very high HDI are remarkable which should be the top priority of interventions for global health policymakers. Also, the health programs should be provided to reduce the burden of this disease in the regions with high incidence and mortality rates of COVID-19.